On the bonding strength of Fe-based self-fluxing alloy coating deposited by different methods on the steel substrate - Feldshtein, Eugene; Kardapolava, Marharyta; Dyachenko, Olga (Zielona Góra: Uniwersytet Zielonogórski)
In the present paper, the bonding strength of Fe-based self-fluxing alloy coating deposited by plasma spraying, gluing and laser remelting and alloying on the steel substrate have been investigated.
Keywords: Fe-based self-fluxing alloy; coatings; plasma spraying; laser remelting; bonding strength